Análisis de imágenes tomadas con resonancia magnetica para la clasificación del Alzheimer utilizando técnicas de Deep Learning (2022)
Nowadays there are more than 50 millions confirmed cases of Alzheimer's disease; the main cause of dementia in adults around the world, commonly miscalled senile dementia. Investigation papers varying in scope, depth and focus are plentiful on the matter of addressing early Alzheimer's disease signs and symptomatology. In regard to recently related signs, these had yell numerous premature detection methods to allow an early diagnosis and treatment. A popular yet suffering from a plethora of under-standardized conditions in the field of studies to indentify its direct or indirect relation with neurodegeneratives diseases, case in point the Alzheimer's disease, an investigatory area filed with numerous breakthroughs albeit accompanied by as many dismissals to its findings and discoveries by the medical community. Separate and divers studies have already employed computer algorithm methods to understand the ever-growing, complex and sizeable data to be analysed with by traditional methods, in order to enhance early diagnosis, or uncover potential new treatments.